spatial and temporal variability of surface temperature, land use and land cover change: a case study in Campinas, Brazil - Marchezan Bezerra, Luiza; Heuminski de Avila, Ana Maria (Revista Brasileira de Climatologia, 2021)
deteriorating climatic conditions in urban centers of Brazil is a real concern for human security and urban livelihood sustainability. The city of Campinas in São Paulo state/Brazil is highly vulnerable to climatic disasters. The present paper analyses the relationship between land use changes and temperature in Campinas between 1989 and 2016. The 28-year period was chosen due to the variability of climatic data in three meteorological stations (University of Campinas, Agronomic Institute of Campinas and International Airport of Viracopos). Data from five sources were used for land use land changes (LULC), and land surface temperature (LST) analysis. The data sources were: i) Landsat 5 Thermometer Mapper (TM), ii) Landsat 5 Thermal Infrared Sensor (TIRS), iii) Thermal Infrared Sensor (ETM +) sensors from Landsat 5, iv) Landsat 8 Operational Land Imager (OLI), and v) Thermal Infrared Sensor (TIRS). The results indicate consistent relations between urbanized increase area and the elevation of air and surface temperature in Campinas. In the studied period, there was an increase of 23% in urbanized areas in Campinas and around the meteorological stations. Cepagri presented the highest growth, about 22%, as well as the station with the highest air temperature